Analysis of Employee Competency at The Education Service of The Sumedang District - Komala Sirotul Zannah; Wawan Gunawan; Rd. Dewi Puspasari (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
Human Resource Management is defined as the science and art of regulating the relationship and role of the workforce so that they can effectively and efficiently use human abilities in order to achieve the goals of each company or agency. Based on the results of observations at the Education Office of Sumedang Regency, it shows that the competence of employees is not fully good. So it is necessary to improve the competence of employees in order to achieve organizational goals. The purpose of this study is to determine the competence of employees at the Education Office of Sumedang Regency and to find out efforts to improve employee competence at the Education Office of Sumedang Regency. The method used is qualitative research methods, using data collection techniques through interviews, observation and documentation, triangulation and the techniques that researchers use in the methodology chapter. To be able to obtain information through this technique, the researchers determined a sample or informant as many as four people including the Head of the Program Sub Division, Head of the General Assets and Personnel Sub Division, General Sub Division Staff, Program Sub Division Staff. With these four informants. Then Based on the results of research through several techniques can be obtained information that researchers have done that the competence of employees is good based on the dimensions of Knowledge, Expertise and Attitude. However, it is necessary to improve the competence of employees at the Sumedang Regency Education Office. Efforts are being made to improve employee competence in the dimensions of expertise with indicators of personal, intrapersonal and communication skills to employees, the provision of rewards and funishmen, where employees can work well considering that if employee performance is appreciated, through the provision of rewards, for employees who excel then competence or work skills also affect the improvement of good performance. It is hoped that the leadership will always try to supervise the work of employees where this will affect the level of competence in the field of employee work expertise.